Nonalcoholic fatty liver disease and health outcomes: An umbrella review of systematic reviews and meta-analyses. (May 2022) - Zhong, Lixian; Wu, Chutian; Li, Yuting; Zeng, Qiuting; Lai, Leizhen; Chen, Sisi; Tang, Shaohui
Purpose: A large number of systemic reviews and meta-analyses have explored the relationship between nonalcoholic fatty liver disease (NAFLD) and multiple health outcomes. The aim of this study is to conduct an umbrella review to assess the strength and evidence for the association between NAFLD and health outcomes. Methods: We systematically identified the present meta-analyses of observational studies reporting an association between NAFLD and health outcomes. For each meta-analysis, we assessed the quality with AMSTAR2 and graded the epidemiologic evidence. Results: Fifty-four articles comprising 111 unique meta-analyses were included in this study. Eighty-five unique outcomes showed significant associations ( P  ← 0.05), whereas 26 unique outcomes showed insignificant associations, and we cannot assess the epidemiologic evidence. For 85 significant health outcomes, four outcomes (carotid intima-media thickness (C-IMT), peak A velocity, left ventricle end-diastolic diameter, incident chronic kidney disease (CKD) in adult patients) was graded as high quality of evidence, 23 outcomes were graded as the moderate quality of evidence, and the remaining 58 outcomes were graded as weak quality of evidence. Fourty-seven (87.03%) studies showed critically low methodological quality. Conclusion: In this umbrella review, only four statistically significant health outcomes showed high epidemiologic evidence. NAFLD seems to relate to an increased risk of C-IMT, peak A velocity, left ventricle end-diastolic diameter, and incident CKD in adult patients.